Treatment of multiple failures in process hazard analysis. Issue 4 (3rd June 2013) - Baybutt, Paul
<x xml:space="preserve">Abstract</x> Process hazard analysis (PHA) is used to identify hazard scenarios. These hazard scenarios may be initiated by single or multiple failures. Other scenario events, such as the responses of safeguards, are also subject to multiple failure, and enabling events may combine with initiating events or other scenario events to produce a type of multiple failure. If multiple failures are not addressed in PHA, important scenarios may be missed, and the risks of scenarios may be underestimated. This article describes the meaning and types of multiple failures that are possible, discusses their importance, and provides an approach for addressing them in PHA. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 361–364, 2013